2014
DOI: 10.1063/1.4871686
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the enhanced flexoelectricity of relaxor ferroelectrics

Abstract: We have measured the bending-induced polarization of Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 single crystals with compositions at the relaxor-ferroelectric phase boundary. The crystals display very large flexoelectricity, with flexocoupling coefficients an order of magnitude bigger than the theoretical upper limit set by the theories of Kogan and Tagantsev. This enhancement persists in the paraphrase up to a temperature T* that coincides with the start of elastic softening in the crystals. Analysis of the temperature d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 33 publications
4
52
0
Order By: Relevance
“…In contrast, Bersuker's theoretical analysis concludes instead that the large flexoelectric response is due to a flexoelectrically-induced alignment of precursor polarization that exists in the paraelectric phase of BTO [18]. In this scenario, BTO would behave similarly to relaxor ferroelectrics [19]. In this article we report a thorough experimental investigation on the magnitude and origin of the enhanced flexoelectricity in BTO single crystals.…”
mentioning
confidence: 93%
“…In contrast, Bersuker's theoretical analysis concludes instead that the large flexoelectric response is due to a flexoelectrically-induced alignment of precursor polarization that exists in the paraelectric phase of BTO [18]. In this scenario, BTO would behave similarly to relaxor ferroelectrics [19]. In this article we report a thorough experimental investigation on the magnitude and origin of the enhanced flexoelectricity in BTO single crystals.…”
mentioning
confidence: 93%
“…Common setups to induce strain gradients in simple geometries include bending of thin films [8][9][10] and compression of truncated pyramids or cones 11,12 . It has been found that flexoelectric coefficients are particularly large in materials with high dielectric constants, such as ferroelectrics 9,11,[13][14][15] . However, the magnitude of these coefficients greatly exceeds theoretical estimates 1, 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the polar nano domain rotation polarization should be dominated to the flexoelectricity in PMN-PT single crystal. 29 As schematically shown in Fig. 4, at free state, the PNRs are randomly distributed in the crystal so that no net polarization can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…The transverse flexoelectric coefficient was calculated to be as high as 100 µC/m at 12 Hz, which is comparable with that of some perovskite ceramics. 5, [12][13][14]29 The error bar of each measurement data in Fig. 2 originates from the small deviation of the collected charge under strain gradient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation